Efficacy of calcium oxide and calcium hydroxide nanoparticles on the elimination of Enterococcus faecalis in human root dentin - Louwakul P. (2017)
© 2016, Springer-Verlag Berlin Heidelberg. Objectives: The objective of this study was to compare the antibacterial effect of calcium oxide nanoparticles (CONPs) and calcium hydroxide nanoparticles (CHNPs) against Enterococcus faecalis in a dentinal block model. Materials and methods: E. faecalis strain JCM 7783 was introduced into dentinal tubules of semicylindrical dentin specimens by centrifugation and incubated for 1 week. Fifty microliters of CONPs or CHNPs was placed on the root canal side of the infected dentin specimens. The specimens were then incubated in aerobic condition at 37 °C and 100 % relative humidity for 1 week. The treated dentin specimens were subjected to fluorescent staining and confocal laser scanning microscopy (CLSM) to analyze the proportions of non-vital and vital bacterial cells inside the dentinal tubules. Scanning electron microscopy (SEM) was used to confirm the effect of the medicaments on the bacteria in the dentinal tubules. Calcium oxide (CO) and calcium hydroxide (CH) were used as controls. Results: Based on the CLSM and SEM analyses, CHNPs were more efficient than CONPs in the elimination of the bacteria in the dentinal tubules. CONPs significantly killed more E. faecalis than CO and CH (P < .05). Neither CO nor CH was able to kill the bacteria. Conclusions: CHNPs were more effective than CONPs in the elimination of E. faecalis in dentinal tubules. Clinical relevance: CHNPs are effective nanoparticles in killing endodontic bacteria present in dentinal tubules. They have potential as an intracanal medicament, which may be beneficial in root canal therapy.